ESTUDO ANALÍTICO E AVALIAÇÃO DA ATIVIDADE ANTIMICROBIANA DO ÓLEO ESSENCIAL EXTRAÍDO DAS FOLHAS DA Pimentta dioica L. - Costa Sobrinho, João Reis Salgado (2008)
The Pimenta dioica Lindl, popularly known as Jamaican pepper, is a native tree from Central America and West India. The tree is a member of Mirtaceae family, can reach 6-15 meters and is found in large scale in Bahia state, northeast of Brazil. Its fruit has an essential oil with great economic value in international market, due its high eugenol level (major compound), which is largely used in chemical and pharmaceutical industries. In this work, it was extracted the essential oil from the leaves of Pimenta dioica Lindl by hydrodestilation process, using a Clevenger's modified system. Some physical properties were determined, like density constancy, refraction index, solubility, color and appearance. Ultra Violet Spectroscopy, FTIR and Mass Spectroscopy were used to identify the major components and these techniques confirmed the eugenol as main compound of Pimenta dioica Lindl. Through the method of external standard using CG, it was possible to quantify the eugenol in the oil. The concentration found was 74% and was confirmed by UV Spectroscopy with similar results. The application of the essential oil from Pimenta dioica Lindl and standard eugenol as bactericide agent as done by Bauer-Kirby method in Escherichia coli, Salmonella sp., Pseudomonas sp. and Vibrio parahaemolyticus. The antibiotics cefotaxima, sulfazotrim, oxacilina and vancomicina were applied as comparison group. The essential oil showed more effectiveness than all antibiotics tested for the microorganism V. parahaemolyticus. For Escherichia coli the oil wasn't so effective than sulfazotrim, but better than the others. The oil was less efficient than sulfazotrin and cefotaxima for the Salmonella sp. and Pseudomonas sp. respectively. In the comparison with all others antibiotics the essential oil showed better results. The eugenol component showed to be the main responsible for the biological action against these microorganisms.